Effect of peritoneal dialysis vs. haemodialysis on respiratory mechanics in acute kidney injury patients - Almeida, Cibele Puato [UNESP]; Balbi, André Luís [UNESP]; Ponce, Daniela [UNESP] (Springer Nature, 2018)
Background: Peritoneal dialysis (PD) and hemodialysis (HD) are options for the treatment of acute kidney injury (AKI) patients. The aim of this study was to compare the effects of PD and daily HD on respiratory mechanics of AKI patients undergoing invasive mechanical ventilation (IMV). Methods: A prospective cohort study evaluated 154 patients, 37 on continuous PD and 94 on HD. Respiratory mechanics parameters such as pulmonary static compliance (Psc) and resistance of the respiratory system (Rsr) and oxygenation index (OI) were assessed for 3 days. Patients were evaluated at moments 1, 2 and 3 (pre- and post-dialysis). Results: The initial clinical parameters were similar in the two groups, except the age that was higher in continuous PD group (70.8 ± 11.6 vs. 60 ± 15.8; p < 0.0001). In both groups, Psc increased significantly, with no difference between the two groups—pre-dialysis (continuous PD 40 ± 17.4, 42.8 ± 17.2, 48 ± 19; HD 39.1 ± 21.3, 39. 5 ± 18.9, 45.2 ± 21) and post-dialysis (continuous PD 42.8 ± 7.2, 48 ± 19, 57.1 ± 18.3; HD 42 ± 19, 45 ± 18.5, 56 ± 24.8). Rsr remained stable among patients on continuous PD (pre-dialysis 10.4 ± 5.1, 13.3 ± 7.7, 13.5 ± 10.3, post-dialysis 13.3 ± 7.7, 13.5 ± 10.3, 11.1 ± 5.9) and decreased among HD patients (pre-dialysis 10.4 ± 5.1, 10.4 ± 5.1, 10.4 ± 5, 1, post-dialysis 10.5 ± 6.8, 10 ± 4.9, 8.9 ± 4.2). There was difference in Rsr between the two groups at the post-dialysis moments 1 and 2 (p = 0.03). OI increased in both groups (continuous PD 260.7 ± 119, 252.7 ± 87.1, 287.3 ± 88.4; HD 228 ± 85, 257 ± 84, 312.1 ± 111.5, p > 0.05), although there was no difference between them. Conclusion: AKI patients undergoing IMV and HD or PD had improvement in the mechanical ventilation and oxygenation, with no difference between the two groups.
Keywords: Acute kidney injury; Continuous peritoneal dialysis; Daily hemodialysis; Oxygenation and invasive mechanical ventilation; Respiratory mechanics